Peningkatan Kemampuan Bahasa Ekspresif Anak Melalui Kegiatan Bermain Peran - Sunarti, Sunarti; Nirwana, Nirwana; Nasaruddin, Nasaruddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This research aims to analyze the influence of role-playing methods in enhancing the expressive language of early childhood children at TK Dua Putra Mahkota. The research uses a qualitative approach with a descriptive method, involving 10 children from group B as research subjects. Data collection techniques were carried out through observation, interviews with teachers and parents, as well as documentation of learning activities. Data were analyzed descriptively qualitatively with steps of data reduction, data presentation, and conclusion drawing. The research results show that the role-playing method can significantly improve children's expressive language skills. Children become more confident in expressing ideas, feelings, and thoughts. In addition, role-playing activities help improve children's vocabulary, articulation, and sentence structure. Observations show an improvement in the child's speaking ability during question-and-answer sessions and storytelling activities in front of the class. Interviews with teachers and parents also revealed that this method is effective in building children's confidence to communicate more fluently. Thus, the role-playing method is recommended as a learning strategy to develop expressive language in early childhood, considering its effectiveness in creating a fun and interactive learning environment.